Adamantinoma: metastatic disease masquerading as a gynaecological malignancy. Issue 6 (3rd June 2021) - Smyth, Sarah; Addley, Susan; Alazzam, Moiad; Soleymani majd, Hooman
Abstract : Adamantinoma is a rare low-grade malignancy of the appendicular skeleton with unclear histogenesis. We present the case of a 65-year-old woman with known recurrent and metastatic right tibial disease despite clear resection margins. On further investigation, a positron emission tomography–CT scan identified a primary breast lesion and an 11 cm mass in the right iliac fossa of suspected ovarian malignancy amenable to surgical resection. The patient underwent total abdominal hysterectomy, bilateral salpingo-oophorectomy and resection of a retroperitoneal mass arising from the pelvic sidewall encompassing the iliac vasculature. The patient made an uneventful recovery with histology confirming disease metastasising to the pelvis. Currently, clinical management guidelines are not available. We present an overview of adamantinoma and highlight a previously undocumented gynaecological oncology surgical approach to this novel disease location. Regarding metastases, we acknowledge the challenges of investigation pertaining to disease site and origin as well as a paucity of recommendations for surveillance and follow-up.